Поліпшення енергетичних характеристик електроприводів з векторним керуванням шляхом компенсації параметричної несиметрії асинхронних двигунів - Мельников, В.О.; Калінов, А.П. (Технічна електродинаміка, 2012)
In this work the vector-controlled system with separate controlled power transfer channels for active and reactive power of each IM phase was presented. The possibility of compensation the IM parametrical asymmetry influence on electric drive energy characteristics by means of decreasing flux linkage in asymmetrical stator phase was shown